2009
DOI: 10.1152/ajprenal.90732.2008
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorates renal failure in 5/6 nephrectomized rats: role of inflammation

Abstract: TNF-alpha and NF-kappaB play important roles in the development of inflammation in chronic renal failure (CRF). In hepatic cells, curcumin is shown to antagonize TNF-alpha-elicited NF-kappaB activation. In this study, we hypothesized that if inflammation plays a key role in renal failure then curcumin should be effective in improving CRF. The effectiveness of curcumin was compared with enalapril, a compound known to ameliorate human and experimental CRF. Investigation was conducted in Sprague-Dawley rats where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
128
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 62 publications
(94 reference statements)
5
128
1
Order By: Relevance
“…CRF was induced in rats by the method published previously (19). Briefly, 5 ⁄6 nephrectomy of rats, weighing between 150 and 200 g, was performed using sterile techniques.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…CRF was induced in rats by the method published previously (19). Briefly, 5 ⁄6 nephrectomy of rats, weighing between 150 and 200 g, was performed using sterile techniques.…”
Section: Animalsmentioning
confidence: 99%
“…It is suggested that many of the beneficial effects of curcumin relate to its ability to suppress both acute and chronic inflammation (4). In our earlier studies, we have shown that curcumin inhibits TNF-␣-dependent NF-B activation and blocks the TNF-␣-mediated downregulation of peroxisome proliferator-activated receptor ␥ (PPAR␥) in mesangial cells (19). A similar effect of curcumin on PPAR␥ and NF-B has been shown in hepatic stellate cells, further supporting the prominent anti-inflammatory effect of curcumin (60).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this method is now being applied to the field of TCM [22][23][24][25][26] , as it could characterize the subtle metabolic interventions induced by TCM in the treatment of diseases and identify the potential implications of TCM. Therefore, in this study, an 1 H NMR-based metabolomic study was applied to investigate the extrarenal therapeutic effects of C sinensis upon 5/6 nephrectomized (5/6Nx) rats (a standard animal model with CKD [27,28] ). First, a C sinensis-dosed 5/6Nx rat group, a 5/6Nx model group and a sham-operated group were established in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in antiglomerular basement membrane nephritis rats, PPAR␥ agonist reduces urinary protein excretion and crescent formation and inhibits glomerular infiltration of monocytes/macrophages (15). Given that renal infiltration of inflammatory cells is an imperative pathomechanism in these disorders (16,17), it is conceivable that PPAR␥ agonists may ameliorate renal injury primarily by inhibiting inflammation rather than by regulating the insulin sensitivity or glucose metabolism. However, the molecular mechanism by which PPAR␥ activation leads to inhibition of renal inflammation remains poorly understood.…”
mentioning
confidence: 99%